STRATEGI PENGEMBANGAN OBJEK WISATA AIR TERJUN DESA MALANGGA KECAMATAN GALANG KABUPATEN TOLITOLI - Fansa, Alfansyah Fathur; Nur, Jabal (MANABIS: Jurnal Manajemen dan Bisnis, 2022)
This study aims to determine the Strategy for Development of Waterfall Tourism Objects in Malangga Village, Galang District, Tolitoli Regency. This study uses a descriptive-qualitative research design. Sources of data in the form of primary data and secondary data, namely data obtained through interviews, as well as documentation related to this research. The data analysis method used is qualitative descriptive analysis, and SWOT. Based on the results of the research and discussion, it can be concluded that in the development of the Waterfall Tourism Object in Malangga Village, it continues to maintain the natural authenticity of the Waterfall object in Malagga Village by utilizing all strengths to seize the maximum opportunity to attract tourists.